Design and Development of Question Data Base and Simulation Tryout System Based on Mobile Apps to Enhance Student Learning Outcomes - Yafie, Evania; Tirtaningsih, Munaisra Tri; Atmoko, Adi; Sari, Zihan Novita (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
One of the most pressing issues in teacher education is the relatively low graduation rate of students enrolled in these programs. This is due to a lack of in-depth knowledge and proficiency in responding to the content and format of teacher certification exams. This study aims to develop a question database and a mobile application-based tryout system to improve student learning outcomes, thereby reducing the graduation rate of teacher education program students. This study employs a development research approach based on the ADDIE model. The research subjects include 120 students for needs analysis, three experts in media, content, and instructional design, and one expert for system feasibility testing. Data collection methods utilize two primary instruments: expert validation and learning outcome tests. The data obtained were then analyzed quantitatively. The research results indicate that the Question Database and Mobile App-Based Practice Test System met validity criteria, with an average score of 94% for media expert validation, 90% for content expert validation, and 93% for instructional design validation. The system feasibility test indicated that the question database application and mobile app-based tryout system were rated “successful” in every application component. This indicates that the application is suitable as a simulation tool for students in the teacher education program. Hopefully, this application can improve learning outcomes and increase the graduation rate among students in the teacher education program.